Immune Checkpoint Inhibitors Have Clinical Activity in Patients With Recurrent Chordoma. Issue 8 (4th October 2022) - Bishop, Andrew J.; Amini, Behrang; Lin, Heather; Raza, Shaan M.; Patel, Shreyaskumar; Grosshans, David R.; Ghia, Amol; Farooqi, Ahsan; Guadagnolo, B. Ashleigh; Mitra, Devarati; Akdemir, Kadir C.; Lazar, Alexander J.; et al.
Abstract : The aim of this study is to evaluate the outcomes and tolerance of immune checkpoint inhibitors (ICIs) for patients with recurrent chordoma. We reviewed the records of 17 patients with recurrent chordomas who received ICIs for progressing disease as part of their treatment between 2016 and 2020. Response was assessed using response evaluation criteria in solid tumors 1.1 criteria. The Kaplan-Meier method was used to estimate the duration of response, progression-free survival (PFS), and overall survival (OS). Clinical benefit was defined as having stable disease (SD), a partial response, or a complete response. The median follow-up from the start of ICIs was 29 months [interquartile range (IQR): 13–35 m]. The majority received pembrolizumab (n=9, 53%), and the median number of cycles delivered was 8 (IQR: 7–12). The 1-year OS was 87%, and the 1-year PFS was 56% with a median PFS of 14 months (95% CI, 5–17 mo). After ICI initiation, most patients (n=15, 88%) had clinical benefit consisting of a complete response (n=1, 6%), partial response (n=3, 18%), and stable disease (n=11, 65%). Among all responders (n=15), the median duration of response was 12 months. Toxicities were limited: 2 (12%) patients having grade 3/4 immune-related toxicities (colitis, grade 3; myocarditis, grade 4). We observed a high rate of clinical benefit and favorable durability from ICI use for patients with recurrent chordoma. These data provide support for the integration of ICIs as a standard first-line systemic therapy option for patients with recurrent chordoma. Prospective studies are warranted to further evaluate efficacy and enhance response rates.